Christian Doctrines and the Death of Osinachi: Social Work Intervention with Women in Intimate Partner Violence in Nigeria. - Imafi, Kelly Alfred (Kabale University, 2024)
This paper x-rayed the spate of Christian doctrines as a resistance for Christian women to stay in violent intimate relationship using Mrs. Osinachi as our case study. It espoused the counsels and teaching of the Christian doctrines and how these are employed to manipulate women to accept and continue to endure the harsh and intimidating relationships with their partner. The paper also established that the custodians of the Christian doctrines who are mainly men amplify the verses of the Bible that focus primarily on women to be submissive while they are silent about the areas that command men not to abuse their wives. The paper adopted literature scoping research method alongside reflexive research method to gather the required data. Content analysis was use to analyzed secondary data which were comprehensively reviewed and important themes isolated and analyzed based on the aim of the study. The paper recommends social work profession that is capable of providing effective intervention to empower and liberate to women from abuse and all forms of religious and cultural oppression which has in the past rendered them voiceless and helpless.